2015
DOI: 10.1513/annalsats.201408-395oc
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia Species Infections in Patients with Cystic Fibrosis in British Columbia, Canada. 30 Years’ Experience

Abstract: B. multivorans and B. cenocepacia have been the predominant Burkholderia species infecting people with CF in Vancouver. The implementation of infection control measures were successful in preventing new acquisition of epidemic strains of B. cenocepacia, leaving nonclonal B. multivorans as the most prevalent species. Historically, survival after infection with B. cenocepacia has been significantly worse than B. multivorans infection, and, of new significance, we show that females tend toward worse clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 46 publications
4
97
0
2
Order By: Relevance
“…1; Zlosnik et al 2015). Bcc isolates were typed by RAPD analyses, which used random primers to generate electrophoretic patterns that differ among divergent isolates (Mahenthiralingam et al 1996;Speert et al 2002a).…”
Section: A Longitudinal Collection Of B Cenocepacia Bacterial Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…1; Zlosnik et al 2015). Bcc isolates were typed by RAPD analyses, which used random primers to generate electrophoretic patterns that differ among divergent isolates (Mahenthiralingam et al 1996;Speert et al 2002a).…”
Section: A Longitudinal Collection Of B Cenocepacia Bacterial Isolatesmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by genome.cshlp.org Downloaded from established protocol Zlosnik et al 2011Zlosnik et al , 2015.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…All Bcc members can trigger chronic airway infections in patients with CF and have emerged as opportunistic pulmonary pathogens (3). Burkholderia cenocepacia and B. multivorans are the two most commonly isolated species (4,5), which are threats for outbreaks. Bcc infections in patients with CF are associated with enhanced morbidity and mortality.…”
mentioning
confidence: 99%
“…The declining prevalence of MRSA in this patient population is exceptional particularly when compared to CF Centres in the USA where there has been a progressive increase in its prevalence over the past 15 years (Cystic Fibrosis Foundation 2015). Consistent with our earlier work, we demonstrated that fewer patients acquired B. cepacia complex infection in the latter part of the study Zlosnik et al 2015), which may reflect stringent infection control 63 practices and the use of antibiotic therapy to attempt to eradicate Burkholderia (Chmiel et al 2014).Nevertheless, new cases of sporadic B. cepacia complex infection continue, emphasising the need for vigilant microbiological surveillance Zlosnik et al 2015).A key finding of our study is the observation of declining prevalence of P. aeruginosa and improving pulmonary function of the transitioning patients. It is likely that aggressive strategies aimed at early identification by increased culture sampling and eradication of P. aeruginosa infection are important components of the improvements in lung function observed here.…”
supporting
confidence: 93%